Mediating Effect of Hope on the Relationship Between Depression and Recovery in Persons With Schizophrenia - Sari, Sri Padma; Agustin, Murti; Wijayanti, Diyan Yuli; Sarjana, Widodo; Afrikhah, Umi; Choe, Kwisoon (Frontiers in Psychiatry, 2021)
Background: Depression and hope are considered pivotal variables in the recovery process of people with schizophrenia. Aim: This study examined the moderating effect of depression on the relationship between hope and recovery, and the mediating effect of hope on the relationship between depression and recovery in persons with schizophrenia. Methods: The model was tested empirically using the data of 115 persons with schizophrenia from Central Java Province, Indonesia. The Calgary Depression Scale for Schizophrenia, Schizophrenia Hope Scale-9, and Recovery Assessment Scale were used to measure participants’ depression, hope, and recovery, respectively. Results: The findings supported the hypothesis that depression moderates the relationship between hope and recovery, and hope mediates the relationship between depression and recovery. Conclusions: The findings suggest that mental health professionals need to focus on instilling hope and reducing depression to help improve the recovery of persons with schizophrenia. Furthermore, mental health professionals should actively develop and implement programs to instill hope and continuously evaluate the effectiveness of the interventions, particularly in community-based and in-patient mental health settings.